2007
DOI: 10.1007/s10592-007-9311-5
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of high pollen dispersal in Eucalyptus wandoo, a dominant tree of the fragmented agricultural region in Western Australia

Abstract: Pollen dispersal was investigated in five remnant populations of Eucalyptus wandoo, a dominant insect-pollinated tree in the fragmented agricultural region of southern Western Australia. Paternity analysis using six microsatellite loci identified a pollen source for 45% of seedlings, and the remainder were assumed to have arisen from pollen sources outside the stands. Outcrossing was variable, ranging from 52 to 89%, and long distance pollen dispersal was observed in all populations with up to 65% of pollen so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
62
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(73 citation statements)
references
References 40 publications
9
62
2
Order By: Relevance
“…This rate of pollen immigration was lower than the rates found for populations of tree species located in more isolated stands: minimum 31.6% in Swietenia humilis, isolated by more than 1 km (White et al, 2002), minimum 33.3% in Eucalyptus wandoo, isolated by 180-1080 m (Byrne et al, 2008), and 39.4% in Sorbus terminalis isolated by 0.4-6 km (Hoebee et al, 2007). The behaviour of pollinators partially determines the distance over which pollen can be dispersed (Dick et al, 2008).…”
Section: Seed and Pollen Immigrationmentioning
confidence: 71%
See 1 more Smart Citation
“…This rate of pollen immigration was lower than the rates found for populations of tree species located in more isolated stands: minimum 31.6% in Swietenia humilis, isolated by more than 1 km (White et al, 2002), minimum 33.3% in Eucalyptus wandoo, isolated by 180-1080 m (Byrne et al, 2008), and 39.4% in Sorbus terminalis isolated by 0.4-6 km (Hoebee et al, 2007). The behaviour of pollinators partially determines the distance over which pollen can be dispersed (Dick et al, 2008).…”
Section: Seed and Pollen Immigrationmentioning
confidence: 71%
“…Bees are capable of long-distance pollen dispersal and can transfer pollen between trees over distances up to several kilometres (Ghazoul, 2005). Studies of tropical beepollinated trees have also reported long-distance pollen dispersal (41 km; White et al, 2002;Dick et al, 2003;Byrne et al, 2008). Native and exotic bees are common insects in the study region, and both Apis mellifera and Trigona spp.…”
Section: Seed and Pollen Immigrationmentioning
confidence: 82%
“…Likewise, although many studies show that insect pollination declines in fragmented populations (Aizen and Feinsinger, 1994), there are cases showing long distance pollination by small insects in fragmented landscapes (41 km; Dick et al, 2003;Byrne et al, 2008). Therefore, despite the expectation that selfing and pollen diversity should be a function of pollinator mobility, in line with the landscape ecology models (Charnov, 1976;Karron et al, 2009), more experimental studies into woody plant density, pollen movement and mating patterns are required to further understand these associations.…”
Section: Generality Of Habitat Fragmentation-mating Pattern Interactionsmentioning
confidence: 99%
“…A strategy for mixing could be based on natural patterns of gene flow, providing opportunities for adaptation and persistence in both established and new environments. In plants, for example, it may be reasonable to simulate leptokurtic gene flow patterns where most propagules disperse proximally but with a significant proportion moving over longer distances (Bacles et al 2006;Nathan 2006;Byrne et al 2007Byrne et al , 2008Sgrò et al 2011). Such an approach would involve mixing locally-sourced material from geneticallyhealthy sources and a smaller proportion of material, depending on natural gene flow dynamics, sourced from more distant populations to increase genetic variation and promote adaptation.…”
Section: Genetic Managementmentioning
confidence: 99%